Social comparison on Instagram, and its relationship with self-esteem and body-esteem - Jacqui Taylor; Georgina Armes (Discover Psychology, 2024)
Abstract Background Previous research has shown that online social comparison can affect perceptions of self-esteem and body image. Purpose of the study This study focussed on social comparison on Instagram and its relationship with levels of self-esteem and body-esteem. Materials and methods Levels of self-esteem and body-esteem were measured using self-report questionnaires, before and after viewing Instagram images eliciting upward, downward, or no comparison. Results Statistical analysis showed self-esteem and body-esteem scores significantly increased after downward comparison, with no change in scores following a neutral condition. Body-esteem scores significantly decreased after upward comparison, whilst self-esteem scores did not. Support for social comparison theory is provided. Conclusions Future research and implications are discussed, such as educating young people about posting and viewing of overly positive images on social media. Social media organisations could provide access to resources which provide advice about mental health issues and support for individuals wanting to discuss body image issues. Future research could potentially establish if participants’ views about eating change after engaging in differing levels of social comparison on Instagram.